2005
DOI: 10.1111/j.1600-0684.2005.00101.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between sex and age class on some physiological, thermal, and hematological indices of the cerrado's marmoset (Callithrix penicillata)*

Abstract: There are few papers about physiological indices in Callithrix penicillata, an increasing primate model in biomedicine. We investigated levels of plasmatic cortisol, plasmatic glucose, free fatty acids, blood cells, tympanic temperature, rectal temperature in C. penicllata, under a fast restraint. Measures of body and weight were accomplished. Males and females were not different regarding any measurements. Body measurements indicated differences between adults and juveniles. Adults showed higher hematocrit an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 25 publications
3
21
0
7
Order By: Relevance
“…The results obtained in our study are similar to the data found in captive C. penicillata, C. jacchus, and C. geoffroyi for all hematological parameters and for some blood chemistry parameters (BOERE et al, 2005;NASCIMENTO et al, 1993;PETERS et al, 2003;YARBROUGH et al, 1984). On the other hand, glucose and serum urea analysis showed higher values than references.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The results obtained in our study are similar to the data found in captive C. penicillata, C. jacchus, and C. geoffroyi for all hematological parameters and for some blood chemistry parameters (BOERE et al, 2005;NASCIMENTO et al, 1993;PETERS et al, 2003;YARBROUGH et al, 1984). On the other hand, glucose and serum urea analysis showed higher values than references.…”
Section: Resultssupporting
confidence: 81%
“…It is a natural and well-known physiological phenomenon in mammals in general, but exceptions occur. For example, in black-tufted marmosets (C. penicillata), there are no hematological differences between males and females (BOERE et al, 2005). However, it is diffi cult to assign if this difference is an artifact of captivity or a true difference between pure C. penicillata and hybrid marmosets.…”
Section: Resultsmentioning
confidence: 99%
“…In our captive adult black tufted‐ear marmosets, basal thermal values obtained via RC and SC routes were significantly higher than those recorded at the left and right TM. The former two had equivalent temperature ranges and were similar to values reported for neotropical primates, including marmosets . RC data reflect deep body temperatures, which in turn are usually higher than those detected at more superficial levels [e.g., ].…”
Section: Discussionsupporting
confidence: 65%
“…Accordingly, the temperature of the marmosets' left and right TM may have been lower than those recorded using the RC and SC routes partly due to the prominent and continuous heat exchange that occurs between the brain and the cerebral/carotid blood flow . It is also important to point out that the thermal values recorded at the left and right TM were similar in range, yet lower than previous reports for this species . While the former result initially suggests a symmetrical cerebral activation during the procedure , pre‐capture baseline TM temperatures are not available and thus individual differences may confound this effect .…”
Section: Discussionmentioning
confidence: 65%
“…Most of them are confined to rhesus monkeys (Macaca mulatta) [Buchl & Howard, 1997;Goodrich et al, 1995;Gotoh et al, 2001;Hassimoto et al, 2004;Herndon & Tigges, 2001;Mythili et al, 2005;Rogers et al, 2005;Smucny et al, , 2004. Only few reports are available on other species of monkeys; in particular, studies on the hematology of New-World species are scarce and always involve single or very few samples per animal [Boere et al, 2005;Malaga et al, 1995;Poleschuk et al, 1998;Riviello & Wirz, 2001;Rosner et al, 1986;Wirz et al, 2000;Yarbrough et al, 1984]. For several years we have been collecting data about hematological parameters in the tufted capuchin monkey (Cebus apella), an arboreal New-World monkey that is widely distributed in South America.…”
Section: Introductionmentioning
confidence: 97%